Power quality enhancement for a grid connected wind turbine energy system with PMSG - Rajasri, Kasula; Kiranbabu, Movva Naga Venkata; Raja, Banda Srinivas; Parvez, Muzammil; Reddy, Govulla Ravi Kumar; Prakash, Nelaturi Nanda; Ahammad, Sk. Hasane; Rajanna, Bodapati Venkata (International Journal of Applied Power Engineering (IJAPE), 2025)
This project investigates the burgeoning potential of gearless wind turbine systems as a pivotal clean energy resource. Unlike conventional gearbox-based turbines, which grapple with issues like frequent breakdowns, intricate repairs, and prolonged downtimes, gearless systems present a suite of advantages. Chief among these is heightened reliability, diminished maintenance costs, and augmented efficiency. By circumventing the need for a gearbox, gearless turbines shed weight, bolster reliability, and demand less upkeep. The incorporation of permanent magnet generators further elevates their efficiency and renders them well-suited for offshore deployment. The emergence of gearless wind turbines heralds a promising frontier for effectively and efficiently harnessing wind power. Their streamlined design and robust performance potential position them as a transformative force in the renewable energy landscape, poised to catalyze substantial advancements towards sustainable energy goals. As research delves deeper into their capabilities and optimization, gearless turbines are poised to emerge as a cornerstone technology in the global pursuit of clean energy solutions.